Pengaruh Lingkungan Tempat Tinggal Terhadap Perilaku Anak - Fedry Saputra (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2017)
The environment where people, either adult or children, live is divided into two; physicalenvironment and abstract environment. Physical environment consists of family, school,and society. Meanwhile, the abstract environment covers the social environment. Thissocial environment is a place where children do numerous activities such as playing,performing daily activities, and practicing religious activities. The influence of environment toward children behaviour is through parenting style either from family, school, or society. A child is born pure, it is the environment that shapes the behavior andcharacter. Parenting through education includes basic education that covers religiouseducation (ukhrawi) like tauhid (the oneness of God), fiqh and akhlak as well as generaleducation like economics and technology. Endogenic factor is an inhereted or innatefactor. An individual possesses this endogenic factor since sperm penetrates the ovum,hence it similar to his/her parents